Impacts of natural and anthropogenic factors on ecosystem health in the basin-mountain transition region: A study based on a risk-process-value assessment framework - Chao Li; Zhao Jin; Li Feng; Chengcheng Jiang; Jianbing Peng (Ecological Indicators)
Ecosystem health in the basin-mountain transition region is highly sensitive to climate change and human activities, making it essential to assess ecosystem health and explore its driving mechanisms. However, few studies have integrated multiple aspects of ecosystem health or explored the pathways by which natural factors and human activities affect ecosystem health. This study introduces a novel comprehensive framework to assess the ecosystem health of Lantian County, which integrates four key aspects: external ecological risks, ecosystem stability, ecosystem service value, and ecosystem processes. In addition, we use Geodetector and Structural Equation Modeling (SEM) to explore the pathways and interactions between natural factors (such as climate and geology) and human activities (especially urbanization), thereby advancing the understanding of the dynamics of ecosystem health. Results indicated that: (1) human activities in Lantian County intensified from 2000 to 2020, aggravating landscape ecological risks in the loess hills. (2) Although soil erosion intensity has decreased and overall ecosystem health improved, significant spatial heterogeneity persisted. By 2020, high-value ecosystem health areas expanded notably in the eastern and southern regions, yet ecological health in the loess hilly areas remained critically low. (3) Natural factors, particularly soil organic carbon, elevation, precipitation, and temperature, exerted significant individual and interactive effects on EHI, while human activities mainly influenced soil erosion intensity and landscape ecological risk. (4) Climate factors are the main drivers of ecosystem health changes, and the intensification of human activities is the main cause of the increased ecological risk in the piedmont transitional zones. The research findings provide new perspectives for understanding the ecosystem health status of basin-mountain transition regions and offer scientific reference for targeted ecological restoration and sustainable management strategies.